2020
DOI: 10.30442/ahr.0604-03-101
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarkers Predictive of Metabolic Syndrome in a Nigerian Population: A Case-Control Study

Abstract: Background: Inflammation is linked to the aetiopathogenesis of Metabolic syndrome (MetS). Objective: To assess the ability of high sensitivity C-Reactive Protein (hs-CRP), Tumour Necrosis Factor-alpha (TNFα) and Interleukin-6 (IL-6) to predict MetS. Methods: A case-control study involving 123 subjects with MetS (cases) and age-matched 123 subjects. without MetS (controls) was conducted. The levels of TNFα, IL-6, and hs-CRP between independent groups were compared. The Receiver Operative Characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In the current study, multivariate logistic regression analyses showed that a unit increase in IL-6 levels elevated the risk of MetS by 9% in the "persistent MetS" group. Previous cross-sectional studies found a positive relationship between IL-6 levels and the prevalence of MetS in the Iranian population [ [56] , [57] , [58] ], including the TLGS community [ 59 ], and in other populations [ [60] , [61] , [62] , [63] , [64] , [65] ]. The convergence of the pathological mechanisms involved in the pathogenesis of MetS leads to a pro-inflammatory state, which explains the increased levels of several inflammatory biomarkers, including IL-6 and CRP, in individuals with MetS.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, multivariate logistic regression analyses showed that a unit increase in IL-6 levels elevated the risk of MetS by 9% in the "persistent MetS" group. Previous cross-sectional studies found a positive relationship between IL-6 levels and the prevalence of MetS in the Iranian population [ [56] , [57] , [58] ], including the TLGS community [ 59 ], and in other populations [ [60] , [61] , [62] , [63] , [64] , [65] ]. The convergence of the pathological mechanisms involved in the pathogenesis of MetS leads to a pro-inflammatory state, which explains the increased levels of several inflammatory biomarkers, including IL-6 and CRP, in individuals with MetS.…”
Section: Discussionmentioning
confidence: 99%